Government of Indonesia’s Battling Strategy to Cope With Pseudo-Cooperatives - Nining I Soesilo (Signifikan: Jurnal Ilmu Ekonomi, 2020)
By contesting the political spectrum versus the economic side of regulation, it is found that the Indonesian cooperative's performance is influenced more by the first approach. As Golkar's electoral vehicle to protect its ruling party's majority vote, the cooperative apex organization (Dekopin) became a parastatal. As a 'bureaucratic capitalist' with state budget support, Dekopin's 'holdup problem' creates the 'subsidy mentality' and increasing corruption perception that stimulated the formation of pseudo-cooperatives. A bottom-up petition to remove Dekopin's parastatal status failed. By calibrating the 2012-2014 panel data, the pseudo-cooperatives decrease when active cooperatives increase. From the 2015 cross-section exercise, pseudo-cooperatives' number rises along with the growing population. External funding to cooperatives is used as a means to spend it on leisure. Many islands show different tendencies of pseudo-cooperatives' creation. In 2016, a government's economic strategy to create healthy cooperatives was started by closing down 32,778 pseudo-cooperatives. This process continued until 2019.JEL Classification: P13, C21, R51, A13How to Cite:Soesilo, N. I. (2020). Government of Indonesia’s Battling Strategy to Cope with Pseudo-Cooperatives. Signifikan: Jurnal Ilmu Ekonomi, 9(2), 219-240. https://doi.org/10.15408/sjie.v9i2.15547.